B(C6F5)3-catalyzed Markovnikov addition of indoles to aryl alkynes: an approach toward bis(indolyl)alkanes. Issue 47 (28th November 2018) - Ling, Fei; Xiao, Lian; Fang, Lu; Feng, Cong; Xie, Zhen; Lv, Yaping; Zhong, Weihui
Abstract : The B(C6 F5 )3 -catalyzed Markovnikov addition of indoles to aryl alkynes was achieved, leading to a wide spectrum of versatile bis(indolyl)alkanes in moderate to good yields with high regioselectivities. Abstract : The first example of the metal- and solvent-free B(C6 F5 )3 -catalyzed Markovnikov addition of indoles to aryl alkynes was disclosed. Both N –H and N -protected indoles were tolerated, leading to a wide spectrum of versatile bis(indolyl)alkanes in moderate to good yields with high regioselectivities.